Budget impact analysis of an early identification and referral model for diagnosing patients with suspected rheumatoid arthritis in Ireland. Issue 2 (13th December 2020) - Kelleher, Dan; Barry, Luke; McGowan, Bernie; Doherty, Edel; Carey, John J; Kane, David
Abstract: Objective: To estimate the budget impact from the perspective of the Irish health-care system attributable to a reconfiguration in the diagnostic care pathway for patients with suspected RA by adopting an early identification and referral model (EIM). Methods: The budget impact model evaluated the total health-care use and costs attributable to an EIM to diagnose patients with suspected RA relative to the reference scenario of current practice. The modelling also assessed a primary outcome of effect, which examined how many patients can be diagnosed by a rheumatologist within 3 months of symptom onset. The budget impact analysis model was estimated over a 5-year time frame. Results: The EIM generated a cost saving for the Irish health-care system of €237 547 over the time frame relative to current practice. The cost savings were realized owing to a reduction in the number of general practitioner (GP) visits of 18 790 and a reduction in diagnostic tests carried out by GPs. The results showed that 1027 (510%) more patients were diagnosed within 3 months of symptom onset in the EIM compared with current practice. Conclusion: This paper has presented an alternative rheumatologist-led service design that can be used in diagnosing patients with suspected RA. The rheumatologist-led service provision detailed in this study has the potential simultaneously to reduce demand for primary care services and to improve the health outcomes of patients. The use of an EIM sees rheumatologist activity incorporate patient demand.